Harmonized Translation: A Case Study from English to Serbian - Perisic, Aleksandar (Educalitra: English Education, Linguistics, and Literature Journal, 2024)
Harmonized translation is not just a process of translation; it is a creative endeavor that transcends simple language conversion. It's a sophisticated method that artfully interweaves the original song’s melody, rhythm, and poetic essence with the target language. This results in a seamless and expressive rendition that resonates with its new audience while preserving the original's musical integrity, emotional resonance, and contextual relevance. In essence, harmonized translation is a profound way of connecting languages and cultures through the power of music, inspiring a new level of creativity in the translation process. Compared to traditional translation theories, which encompass lyrics and poems as discussed by Munday, J. (2016), harmonized translation emphasizes measurable qualities necessary for achieving what can succinctly be described as fidelity.